The Process Of Quality Education - As A Mechanical Combination Of Teaching And Learning Processes - Rustam Abdullayev (Procedia of Social Sciences and Humanities, 2022)
Quality education depends on the fact that students are well educated. Therefore, the educational process is a combination of educational and pedagogical tasks. One of the factors confirming theintegrity of the educational and pedagogical tasks of education is the fact that teaching methods are expressedas an integral part of teaching methods, and secondly, educational methods themselves are manifested asmethods of motivating learning.